Fecal microbiota transplantation provides insights into the consequences of transcriptome profiles and cell energy in response to circadian misalignment of chickens - Siyu Chen; Hao Liu; Chao Yan; Yushan Li; Jinlong Xiao; Xingbo Zhao (Poultry Science, 2024)
ABSTRACT: The circadian misalignment (CM) disordered circadian rhythms exert adverse effects on animals. Poultry as one of animals suffers health and welfare problems due to long-term lighting photoperiods caused by CM. However, the roles of CM on organ development, cell growth, metabolism and immune are still unclear in chickens. In this study, a Chinese dual-purpose native breed, was used to explore the effects of CM on transcriptomic pattern of brain and cell energy biogenesis, and further fecal microbiota transplantation (FMT) was applied to investigate its “therapy” effect from CM suffering. Our results showed that the CM led to stunting in brain and small intestine of chicken. CM decreased of cell proliferation, and energy production, mtDNA copies and expression of genes related to cell cycle or mitochondrial biogenetics, while it upregulated the reactive oxygen species (ROS) level and the sensitivity to inflammation. Interestingly, FMT rescued the organ developmental defects and cell dysfunctions induced by CM. Circadian misalignment brought about abnormal tissue and cell developments, energy biogenesis, and immune response in birds. This study provided a comprehensive perspective on understanding the regulation of CM and FMT on bird development and welfare.